Trends in income and wealth inequalities - Pascale Bourquin; Mike Brewer; Thomas Wernham (Institute for Fiscal Studies (IFS), 2022)
This chapter brings together trends in inequalities in income, wealth and, to a limited extent, consumption in the United Kingdom, with a focus on trends until the onset of the COVID-19 pandemic.
Keywords: 330; Poverty; inequality and social mobility; Inequality; Wealth; Pay